The development and validation of the clinicians’ awareness towards cognitive errors (CATChES) in clinical decision making questionnaire tool - Chew, K.S.; Yee Cheng, Kueh; Adlihafizi, Abdul Aziz (Biomed Central, 2017)
Background: Despite their importance on diagnostic accuracy, there is a paucity of literature on questionnaire tools to assess clinicians’ awareness toward cognitive errors. A validation study was conducted to develop a questionnaire tool to evaluate the Clinician’s Awareness Towards Cognitive Errors (CATChES) in clinical decision making. Methods: This questionnaire is divided into two parts. Part A is to evaluate the clinicians’ awareness towards cognitive errors in clinical decision making while Part B is to evaluate their perception towards specific cognitive errors. Content validation for both parts was first determined followed by construct validation for Part A. Construct validation for Part B was not determined as the responses were set in a dichotomous format. Results: For content validation, all items in both Part A and Part B were rated as “excellent” in terms of their relevance in clinical settings. For construct validation using exploratory factor analysis (EFA) for Part A, a two-factor model with total variance extraction of 60% was determined. Two items were deleted. Then, the EFA was repeated showing that all factor loadings are above the cut-off value of >0.5. The Cronbach’s alpha for both factors are above 0.6. Conclusion: The CATChES questionnaire tool is a valid questionnaire tool aimed to evaluate the awareness among clinicians toward cognitive errors in clinical decision making.